2018
DOI: 10.1507/endocrj.ej17-0508
|View full text |Cite
|
Sign up to set email alerts
|

Increased secreted frizzled-related protein 4 and ficolin-3 levels in gestational diabetes mellitus women

Abstract: Abstract. By biochemical and epidemiological similarity with type 2 diabetes mellitus (T2DM), gestational diabetes mellitus (GDM) has some overlap between prediction markers and risk factors of T2DM. The present study aimed to establish that secreted frizzled-related protein 4 (SFRP4) and ficolin-3 levels, which have been linked to insulin resistance and the development of T2DM, are elevated in GDM women. A longitudinal prospective cohort study of 86 GDM and 273 normal glucose tolerant (NGT) pregnant women was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…With respect to this glucose resistance, sFRP4 is increased during GDM in the second trimester (i.e. �14 weeks) [52,53]. Interestingly, increased serum concentrations of sFRP4 were observed years before the diagnosis of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to this glucose resistance, sFRP4 is increased during GDM in the second trimester (i.e. �14 weeks) [52,53]. Interestingly, increased serum concentrations of sFRP4 were observed years before the diagnosis of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Most biomarkers were assessed only once during pregnancy between the 14 th and the 41 st week of gestational age. Twelve articles reported multiple biomarker assessment timepoints: ten studies evaluated biomarkers two times [ 19 28 ], and two on three occasions [ 29 , 30 ]. More than 150 biomarkers were evaluated, as listed in full in Additional file 4 .…”
Section: Main Textmentioning
confidence: 99%
“…Furthermore, Xiao-song Yuan et al reported that higher levels of ficolin-3 are associated with the risk of GDM. This increased level of ficolin-3 during the en-tire pregnancy period could be an important risk factor for this pregnancy complication [34]. This controversial discussion might result from different research objects or detection methods of ficolin-3 levels.…”
Section: Serum Ficolin-3mentioning
confidence: 99%